Husbands’ and wives’ risk preferences and improved maize adoption in Tanzania - Magnan, Nicholas; Love, Abby M.; Mishili, Fulgence J.; Sheremenko, Ganna (International Association of Agricultural Economists, 2020)
Research on technology adoption typically assumes that the preferences of a single individual—the household head—determine household‐level decisions. This study uses experimentally derived prospect theory‐based risk preferences from couples in Tanzania to test whether men's and women's risk preferences, which often diverge, influence the adoption of improved maize varieties. We find that women's risk aversion and men's loss aversion are negatively correlated with improved variety use. The tendency of men to overweight small probabilities is negatively associated with adoption, whereas the tendency of women to do so is positively associated. These findings suggest that technology adoption research should look beyond the preferences of the household head, and that technology promoters should consider targeting both men and women in their education and dissemination efforts.